Lao People's Democratic Republic : 2008 Article IV Consultation; Staff Report; Staff Supplement; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that Lao People's Democratic Republic's (PDR) economy has performed well in recent years, owing to generally stable macroeconomic conditions and a rapidly expanding natural resource sector. Real GDP growth has averaged more than 7 percent since 2004. Growth is projected to reach 7 1\2 percent in 2008, driven by similar factors as last year, as well as higher mining output. The medium-term outlook for Lao PDR remains positive, but hinges on sound development of the resource sector and other steps to strengthen competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet